Predictable communities of soil bacteria in relation to nutrient concentration and successional stage in a laboratory culture experiment - Woojin Song; Mincheol Kim; Binu M. Tripathi; Hyoki Kim; Jonathan M. Adams (Environmental Microbiology, 2016)
Summary It is difficult to understand the processes that structure immensely complex bacterial communities in the soil environment, necessitating a simplifying experimental approach. Here, we set up a microcosm culturing experiment with soil bacteria, at a range of nutrient concentrations, and compared these over time to understand the relationship between soil bacterial community structure and time/nutrient concentration. DNA from each replicate was analysed using HiSeq 2000 Illumina sequencing of the 16 S r RNA gene. We found that each nutrient treatment, and each time point during the experiment, produces characteristic bacterial communities that occur predictably between replicates. It is clear that within the context of this experiment, many soil bacteria have distinct niches from one another, in terms of both nutrient concentration, and successional time point since a resource first became available. This fine niche differentiation may in part help to explain the coexistence of a diversity of bacteria in soils. In this experiment, we show that the unimodal relationship between nutrient concentration/time and species diversity often reported in communities of larger organisms is also evident in microbial communities.